2010
DOI: 10.1001/dmp-v4n2-hcn10003
|View full text |Cite
|
Sign up to set email alerts
|

Ready, Willing, and Able: A Framework for Improving the Public Health Emergency Preparedness System

Abstract: ABSTRACTEvery society is exposed periodically to catastrophes and public health emergencies that are broad in scale. Too often, these experiences reveal major deficits in the quality of emergency response. A critical barrier to achieving preparedness for high-quality, system-based emergency response is the absence of a universal framework and common language to guide the pursuit of that goal. We describe a simple but comprehensive framework to encourage a focused conversation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 37 publications
(69 reference statements)
3
55
0
Order By: Relevance
“…More complex study designs and the inclusion of other variables not studied here, such as the funding available for MFI planning at the jurisdictional level and MFI training and knowledge of the ME/C, are needed in order to better characterize the factors related to preparedness. Our three-tiered approach to measuring preparedness contrasts with other models for systems-level preparedness, which have been suggested, such as the Ready, Willing, and Able framework developed by McCabe and colleagues [44]. Our approach incorporates many of their constructs, especially "Ability", which is reflected in our operational capabilities measure.…”
Section: Discussionmentioning
confidence: 99%
“…More complex study designs and the inclusion of other variables not studied here, such as the funding available for MFI planning at the jurisdictional level and MFI training and knowledge of the ME/C, are needed in order to better characterize the factors related to preparedness. Our three-tiered approach to measuring preparedness contrasts with other models for systems-level preparedness, which have been suggested, such as the Ready, Willing, and Able framework developed by McCabe and colleagues [44]. Our approach incorporates many of their constructs, especially "Ability", which is reflected in our operational capabilities measure.…”
Section: Discussionmentioning
confidence: 99%
“…Local public health agencies have a median staff size of 13 [22], which emphasizes the imperative that all workers are ready, willing, and able to respond to a public health emergency if needed [6]. The diminishing numbers of U.S. public health workers [14] reinforce the need to ensure that LHD employees are sufficiently committed to responding during an emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have pointed to WTR as a function of the interplay between perceptions of threat and efficacy toward a hazard [4,5]. Research has also identified WTR as a requisite for quality in public health systems' response efforts, as response willingness is fundamental to response capacity [6]. Examples in which low WTR had the potential to hinder public health and healthcare response to an infectious disease outbreak have been reported [4,7-11].…”
Section: Introductionmentioning
confidence: 99%
“…24 The specific questions and operational criteria for the three constructs in the order they evolved and were assessed were: 24 The specific questions and operational criteria for the three constructs in the order they evolved and were assessed were: …”
Section: Data Collection and Measuresmentioning
confidence: 99%